Eco‐evolutionary dynamics in response to selection on life‐history. (8th April 2013) - Cameron, Tom C.; O'Sullivan, Daniel; Reynolds, Alan; Piertney, Stuart B.; Benton, Tim G.; Sorci, Gabriele
Abstract Understanding the consequences of environmental change on ecological and evolutionary dynamics is inherently problematic because of the complex interplay between them. Using invertebrates in microcosms, we characterise phenotypic, population and evolutionary dynamics before, during and after exposure to a novel environment and harvesting over 20 generations. We demonstrate an evolved change in life‐history traits (the age‐ and size‐at‐maturity, and survival to maturity) in response to selection caused by environmental change (wild to laboratory) and to harvesting (juvenile or adult). Life‐history evolution, which drives changes in population growth rate and thus population dynamics, includes an increase in age‐to‐maturity of 76% (from 12.5 to 22 days) in the unharvested populations as they adapt to the new environment. Evolutionary responses to harvesting are outweighed by the response to environmental change ( 1.4 vs. 4% change in age‐at‐maturity per generation). The adaptive response to environmental change converts a negative population growth trajectory into a positive one: an example of evolutionary rescue.